PENGARUH PEMAHAMAN SISTEM PGM-FI TERHADAP HASIL PRAKTIK TUNE-UP SISWA KELAS XI TSM SMK PANCASILA 1 KUTOARJO - Muhammad Nur Rohman Fajri; Dwi Jatmoko; Aci Primartadi (STKIP Subang, 2026)
This study aims to determine: (1) the level of students’ understanding of the PGM-FI (Programmed Fuel Injection) system; and (2) the effect of PGM-FI system understanding on tune-up practical outcomes among Class XI TSM students at SMK Pancasila 1 Kutoarjo. A quantitative approach with an ex post facto correlational design was employed. The subjects were 30 Class XI TSM students in the 2025/2026 academic year. Data were collected using a 40-item written test on PGM-FI understanding and a 5-component practical performance observation sheet. Instruments were validated using Pearson Product Moment correlation (r-table = 0.361; all items valid) and reliability-tested using Cronbach’s Alpha (α = 0.898) for the written test and Cohen’s Kappa (κ = 1.000) for the practical sheet. Prerequisite tests confirmed normality (K-S sig. = 0.110 > 0.05) and linearity (Deviation from Linearity sig. = 0.117 > 0.05). Results showed that PGM-FI understanding was in the high category (mean = 32.57; 81.43%), as was practical performance (mean = 80.67; high category). Simple linear regression and Pearson correlation confirmed a positive and significant effect of PGM-FI understanding on tune-up practical outcomes (r = 0.493; R² = 0.243; t = 3.002; sig. = 0.000 < 0.05), with PGM-FI understanding contributing 24.3% to the variation in practical outcomes. The remaining 75.7% is attributable to other factors such as practical experience, motivation, facilities, and individual student characteristics.